Theology of the Economy as Fundamental Theology - Tognato, Carlo (2003)
The encounter between theology and economics is generally addressed by theologians as a question that falls within the scope of moral theology. This article will take a step aback with respect to this trend and discuss in what sense –from a logical standpoint– such a disciplinary encounter is a matter of fundamental theology even prior to being a matter of moral theology.